Комунікативні тактики інтимізації у англомовному художньому дискурсі - Палійчук, Анна Леонардівна; Paliychuk, Anna (Харків : ХНУ, 2012)
У статті розглянуто комунікативні тактики інтимізації та засоби їх втілення у англомовному художньому дискурсі. Визначено ідіостильові особливо реалізації комунікативних тактик інтимізації у текстах коротких оповідань О. Генрі, К. Менсфілд та С. Моема. The article deals with the intimization communicative tactics and means of their implementation in the English literary discourse. The peculiarities of the intimization communicative tactics usage, according to the author`s individual style, are determined on the basis of O. Henry, K. Mansfield and S. Maugham short stories.
Intimization Communicative Tactics in the English Literary Discourse
Keywords: автор; дискурс; ідіостиль; інтимізація; комунікативна стратегія; комунікативна тактика; читач; author; discourse; individual style; intimization; communicative strategy; communicative tactics; reader